CRAFT ACTIVITY DURING AND POST-PANDEMIC UNDER THE FOCUS OF THE ORANGE ECONOMY (LACCEI, 2024)
This document will show the variables that significantly affect the economic activity of handicrafts in general and in the post-pandemic period. This craft activity is an important item for many regions, being carried out with ancestral knowledge transmitted from generation to generation. The study was carried out through the multivariate analysis of multiple correspondence, with data obtained from surveys and interviews applied to artisans from the municipality of Ráquira Boyacá - Colombia, as a representative sample of the behavior of the sector. With the data and the analysis carried out, it can be concluded that this sector has great potential to take advantage of the benefits of the orange economy after the pandemic, but for this to be possible, they must be trained and taught how to access said benefits contemplated in the Law in different countries